Quality of life: Ranking and assessment of twenty populous districts of Uttar Pradesh - Nitin Kumar Mishra,; Ashutosh Singh,; Himanshu Tiwari, (National Geographical Journal of India, 2025)
The comprehensive development of an urban region encompasses various characteristics, including access to essential amenities, infrastructure, economic factors, and environmental circumstances. Contemporary economic and industrial metrics contribute to social stability by alleviating poverty and enhancing resource accessibility, hence lowering social disputes and promoting community cohesion. The Quality of Life (QoL) score was generated by principal component analysis (PCA) to evaluate the overall development of 20 populous districts in Uttar Pradesh. The score is determined by 17 indications categorized into six factors. This research examines the multifaceted quality of life in the twenty leading districts of Uttar Pradesh through six comprehensive indices: 1) Basic Amenities Index (BAI), 2) Infrastructure Role Index (IRI), 3) Gender Parity Role Index (GPRI), 4) Economic Parameter Index (EPI), 5) Industrial Factor Index (IFI), and 6) Environmental Factor Index (EFI). Districts were categorized as top, average, or low performers based on the statistical metrics of mean (μ) and standard deviation (σ). The data reveal substantial disparities in growth among districts, with Ghaziabad, Lucknow, and Kanpur Nagar consistently excelling in multiple indices, signifying robust economic, industrial, and infrastructural foundations. Conversely, districts such as Sitapur and Azamgarh exhibit subpar performance for fundamental utilities, economic metrics, and environmental sustainability. The evaluation also underscores substantial advancements in gender equity in areas such as Prayagraj and Varanasi. These findings underscore the necessity of focused interventions to mitigate regional disparities, enhance living standards, and foster equitable development in Uttar Pradesh. This research provides policymakers with significant information for prioritizing investments in underperforming regions and ensuring equitable growth.